Impairment of mitochondrial function of rat hepatocytes by high fat diet and oxidative stress - Garnol, T; Endlicher, R; Kučera, O; Drahota, Z; Cervinková, Z (Physiological research, 2014)
Fatty liver disease associated with obesity is an important medical problem and the mechanisms for lipid accumulation in hepatocytes are not fully elucidated yet. Recent findings indicate that mitochondria play an important role in this process. Our data on hepatocytes in which mitochondria are in contact with other cytosolic structures important for their function, extend observations obtained on isolated mitochondria and confirm inhibition of Complex I activity in hepatocytes isolated from rats fed by high fat diet (HFD) compared with controls fed by standard diet (STD). Furthermore we have found that HFD-hepatocytes are more sensitive to the peroxidative stress because under these conditions also Complex II activity is disturbed. Therefore in HFD animals decrease of Complex I activity cannot be compensated by Complex II substrates as in STD hepatocytes. Our data thus indicates that combination of HFD and peroxidative stress potentiates HFD damaging effect of mitochondria because both branches of the respiratory chain (NADH- and flavoprotein-dependent) are disturbed.
Keywords: hepatocyty; Male; Diet, High-Fat; Rats; Rats, Wistar; Hepatocytes; krysa rodu Rattus; Mitochondria, Liver; jaterní mitochondrie; dieta s vysokým obsahem tuků; mužské pohlaví; Oxidative Stress; Animals; potkani Wistar; zvířata; oxidační stres